Analysis of a Novel Magnetic-Geared Dual-Rotor Motor With Complementary Structure - Sun, Le; Cheng, Ming; Jia, Hongyun (IEEE transactions on industrial electronics (1982), 2015)
A permanent-magnet dual-rotor motor is particularly suitable for constructing the power split device in hybrid electric vehicle application. This paper proposes a new magnetic-geared dual-rotor motor (MGDRM) design with complementary structure, in which both the inner and outer rotors are divided into three modules with a proper angular displacement for each other along the axis direction. This complementary design makes the flux linkage symmetrical and total cogging torque significantly reduced, without impairing the torque production. A simplified magnetic circuit model is developed to illustrate the complementary principle. By finite-element analysis (FEA), the effectiveness of such complementary structure is verified through the comparison with the conventional design. A prototype motor has been manufactured, and experiments have been carried out. Both FEA and experiments show that this new MGDRM offers symmetrical back-EMF waveforms, smaller cogging torque, and lower torque ripple.